Role of Selective Interaction in Wealth Distribution (Communications in Computational Physics, 2006)
In our simplfied description 'wealth' is money (m). A kinetic theory of a gas like model of money is investigated where two agents interact (trade) selectively and exchange some amount of money between them so that the sum of their money is unchanged and thus the total money of all the agents remains conserved. The probability distributions of individual money (P(m) vs. m) is seen to be influenced by certain ways of selective interactions. The distributions shift away from Boltzmann-Gibbs like the exponential distribution, and in some cases distributions emerge with power law tails known as Pareto's law (P(m) \u221d m\u2212(1+\u03b1)). The power law is also observed in some other closely related conserved and discrete models. A discussion is provided with numerical support to obtain insight into the emergence of power laws in such models.